2008
DOI: 10.1590/s0103-50532008000700027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using mixed initiator systems on the efficiency of photopolymerization of dental resins

Abstract: Foi realizado um estudo para determinar a eficiência da utilização simultânea dos fotoiniciadores fenilpropanodiona (PPD) e canforquinona (CQ) para a polimerização de polímeros acrílicos e avaliar possíveis mecanismos que levem à sinergia ou antagonismo. Foi encontrado que as eficiências de ambos iniciadores usados individualmente são maiores que a da mistura, indicando que quando os iniciadores são usados simultaneamente há uma transferência de energia do iniciador mais eficiente (CQ) para o menos eficiente (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The IR spectrum of 5a (KBr, cm -1 ) showed strong absorption bands at 1700 (C=O), 1577 (C=N), and 1463 (P-Phenyl) (17) . The 1 H NMR spectrum of 5a (CDCl 3 ,  ppm) showed signals at 0.99 (s, 3H, CH 3 (C=O). A signal at δ =15.5 ppm was observed in its 31 P NMR which fits with the phosphorane on a four -membered ring (18,19) .…”
Section: T Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectrum of 5a (KBr, cm -1 ) showed strong absorption bands at 1700 (C=O), 1577 (C=N), and 1463 (P-Phenyl) (17) . The 1 H NMR spectrum of 5a (CDCl 3 ,  ppm) showed signals at 0.99 (s, 3H, CH 3 (C=O). A signal at δ =15.5 ppm was observed in its 31 P NMR which fits with the phosphorane on a four -membered ring (18,19) .…”
Section: T Results and Discusionmentioning
confidence: 99%
“…The infrared spectra were recorded in KBr disks on a Jasco Fourier Transform Infrared Spectrophotometer model FT/IR-3000E. The 1 H NMR spectra were recorded in deuterated CDCl 3 or DMSO on JEOL JNM-EX 270 (at 270 MHz) and /or JEOL 500 AS (at 500 MHz) Spectrometer using TMS as an internal reference. 13 C NMR spectra were recorded on JEOL500 AS (at 125 MHz).…”
Section: Methodsmentioning
confidence: 99%
“…An explanation for this difference could be the high photoinitiator concentrations used by these authors (1.8% in weight with a 1 : 1 ratio) [18]. In contrast, Neumann et al [44,45] observed lower conversions 6 Journal of Spectroscopy for the PPD and CQ photoinitiators, which suggests a possible reaction between PPD and the resinous matrix, which altered the absorption values and could have been caused by an altered conformation in the carbonyl groups. Therefore, the first hypothesis for this study is incorrect because the resin with both photoinitiators (CQ + PPD) yielded a lower DC than the resin containing only CQ.…”
Section: R1 and R3 (Referring Tomentioning
confidence: 87%
“…5,6 Monomers, the photoinitiating system and fillers constitute a set of parameters that influence the photopolymerization kinetics, volume shrinkage and mechanical properties of the composite material. [7][8][9][10][11][12][13][14][15] Additionally, composite properties are well known to be influenced by the resin-filler interface. Thus, for example, the grafting of low-polar groups onto silanol functions on silica particle surface limits the formation of hydrogen bonds, which lead to aggregation, allowing a better dispersion of the filler in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%